(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This research proposes a theoretical framework for a distinctly Nigerian approach to theatre direction, arguing for the conscious synthesis of indigenous Nigerian performance aesthetics with postcolonial dramaturgical strategies. It critiques the continued dominance of Western directorial models—rooted in proscenium arch conventions, psychological realism, and Aristotelian structures—as a lingering effect of cultural colonialism that fails to fully express the Nigerian worldview. The study posits that a decolonized Nigerian theory of directing must instead be architected from the principles found in the nation’s rich performance traditions, such as Yoruba Alárìnjó, Igbo Mmanwu, and Hausa Wassan Kara. These principles include a non-linear narrative structure, the intimate and participatory relationship between performer and spectator, the integral fusion of music, dance, and masquerade with text, and the spiritual dimension of performance. By engaging with postcolonial theory (Fanon, Bhabha) and African theatrical paradigms (Soyinka’s “Fourth Stage,” Ngũgĩ’s “Decolonising the Mind”), this paper constructs a new directorial lexicon. The ultimate aim is to move beyond mere adaptation and establish an authentic, foundational theory that empowers Nigerian directors to create work that is philosophically, culturally, and aesthetically rooted in their own heritage.